A note on the price- and cost structure of retail payment services in the Swedish banking sector 2002 - Guibourg, Gabriela; Segendorff, Björn (Journal of Banking & Finance, 2007)
We estimate private costs in the Swedish banking sector for the production of payment services and investigate to what extent the price structure reflects the estimated cost structure. We find that (i) banks tend to use two-part tariffs but (ii) variable costs are poorly reflected in transaction fees towards both consumers and corporate customers. (iii) There exist large cross subsidies between different payment services, foremost from acquiring card payments to cash distribution to the public, while payment services as a whole are not subsidized.